Unification of selection by quantitative characters in seed production of green pea (Pisum sativum L. partim) - В. М. Стригун (Plant Varieties Studying and Protection)
In the production of original, basic green pea seed it is critical to to single out (select) basic plants. The marked (selected) plants shall comply with their breeder’s description. Since seed breeding events are conducted with every new variety by various persons and in various agroecologic conditions, subjective factors, as well as environmental factors, may interfere with determining parameters of every characteristic considered there. As a consequence, identification and varietal characteristics and properties are subject to change and might not correspond to the breeder’s description; this, of course, affects the quality of variety. For the purpose of leveling the above factors, example of vegetable pea serves as a suggestion of a technique for exeminig parameters of variability of quantitative traits for specific population observing the rule of «golden section».